Evaluation of the Innovational Development in Russia’s Arctic area - K. N. Arkhipova (Модернизация, инновация, развитие, 2019)
Purpose: the aim of the thesis – analyze the innovation development of the regions belonging to the Russian’s Arctic area.Methods: the methodological foundations of the research are based on modeling scenarios, analysis of open statistical sources, projected estimates and calculations, projected methods. As open statistical sources were used the data of the official statistics, analytical materials of international organizations, federal and regional authorities.Results: the result of the study is existing methods for assessing the innovative development of the regions, analyze of the innovation development among regions belonging to the Russian’s Arctic area. In addition, on the basis of the calculations carried out, the advantages and obvious drawbacks of the methods common today, as well as the presence of a connection between them, were identified.Conclusions and Relevance: the calculations, which allow to evaluate the innovative development, showed that in the regions of the circumpolar zone there is a low level of innovative development, which in turn becomes an obstacle to the implementation of large investment projects for the development of new fields. In such conditions, it is necessary to create research and development sites, however, since there are no prerequisites, not in the territory of the Arctic zone, but adjacent regions, where prerequisites for scientific research have already been created.